PERTANGGUNGJAWABAN PIDANA DISABILITAS YANG MELAKUKAN PENGANIAYAAN - Ardika, Ridho (Legal Standing : Jurnal Ilmu Hukum, 2024)
The Criminal Code has explained the responsible ability of a person with a disability in article 44 paragraphs 1 and 2, while in Law No. 1 of 2023, Discuss more specifically about disability criminal liability, according to court decision No. 57 / Pid.B / 2021 / PN. Kba involving a person with a mental disability who molested his own sibling. The purpose of this study is to determine the accountability of criminal acts of maltreatment committed by disabilities in the perspective of Criminal Law and Islamic Criminal Law and use Law No. 1 of 2023 as a comparison with the Criminal Code. The research method used in this study is the normative juridical method using a legal approach, a conceptual approach and a comparative approach. Criminal responsibility for perpetrators of abuse committed by disabilities in the Islamic Criminal Law a person is considered responsible if he has the ability to think and choose (idrak and ikhtiar). Meanwhile, in the Criminal Law, a person with a disability cannot be held accountable for his mental disability, then in Law No. 1 of 2023, an intellectual or mental disability cannot be convicted if he has reached moderate to severe levels. In court decision No.57/Pid.B/2021/PN. The accused should not be punished because his soul was disturbed during his growth or because he was in a mental hospital if his actions could not be held accountable.